Feasibility assessment of algae methyl esters as an alternative source of biofuels a project study - Jimenez, Princess; Lansang, Jezza Mae; Odevilas, Glo Ann; Revote, Vincent
Algae methyl esters have the potential to thrive in the biodiesel market. The Biodiesel Act of 2006 had a significant effect on firms selling methyl esters to be blended with regular diesel. As such, annual mandated increase of percent blends in biodiesel is an opportunity for algae methyl esters to penetrate the market. We show that annual demand for Biodiesel in the Philippines steadily increases with a major jump between the years 2013 to 2014 due to an expected mandate. The current aggregated supply rate, however, cannot meet the projected demand. We present a Business to Business (B2B) marketing strategy to enter the market in term of product positioning, location channels, and promotions aimed at our business customers. Sales forecast shows significant sales volume within each year. Technological advances have made producing Algae Methyl Esters possible. The current technology can produce an output of 3,783,591 Liters of methyl esters in just a land area of 3,373 square meters, answering 1.5% of the country's demand-supply gap. We discuss production processes required to produce the product. With the ability to mitigate carbon and multiplicative growth of the algae, sustainability is foreseen. Total project cost for accomodating 1.5% of the Philippines's demand-supply gap is projected to be Php. 370,681,066. Expected revenue forecast was determined to be 2,270,155 Liters in 2011 and an all-time high of 3,783,591 Liters in 2015. With this sales forecast, the project can generate an income of Php. 56,521,881 in 2011, Php 80,822,964 in 2012, Php. 118,053,339 in 2013, Php. 154,513,714 in 2014, and Php. 156,333,714 in 2015. Return of assets in 2011 is 0.2352 and 0.1728 in 2015. Debt-Equity ratio is determined to be 0.2352 in 2011 and 0.1728 in 2015. Asset turnover is determined to be 0.9135 in 2011 and 0.4045 in 2015. The payback period for the project is calculated to be around three years with a selling price of Php. 85.00. We show that in addition to financial benefits, algae methyl esters also have socio-economic benefits. We integrated project costs from producing the product and weighted the social and economic benefits. National objectives such as maximizing labor, minimizing waste and minimizing foreign exchange is presented. Cost is valuated to be Php. 58,369,778 in the zeroth year and Php 31,974,400 from the first to the fifth year. Benefits are valuated to be Php. 56,388,372 for every year. Net Present Value and Internal Rate of Return is favorable to the existence of the company. We show that with the project undertaking, social benefits to the local community is possible.